Effect of Infliximab on the UVB-Induced Apoptosis of Keratinocytes Infected by HPV38 E6/E7. (25th February 2013) - Aubin, François; Gheit, Tarik; Prétet, Jean Luc; Tommasino, Massimo; Mougin, Christiane
Abstract : The question of the effect of anti-TNF-alpha in skin carcinogenesis is especially relevant in view of the increased use of these drugs for the treatment of autoinflammatory immune diseases. Since ultraviolet radiation and human papillomavirus are involved in skin carcinogenesis, we wished to investigate the effect of TNF-alpha antagonists on the UVB-induced apoptosis of keratinocytes infected by HPV38. Our results indicate that anti-TNF agent, infliximab, does not contribute to the survival of HPV38-transduced keratinocytes with UVB-induced DNA damages.